Kepatuhan Ibu Hamil Mengkonsumsi Tablet Fe Dengan Kejadian Anemia Di Wilayah Kerja Puskesmas Aranio - Fakhriyah Fakhriyah; Husnul Khatimah; Nina Rahmadiliyani; Nurul Hayati (HB PRESS, 2018)
According to WHO, 40% of maternal death in the developing countries related to anemia in a pregnancy. The highest factor which influence anemia occurrence is obedience in consuming Fe tablet i.e 60% compare to other factors. The aim of this research is to know the relationship between obidiencein consuming Fe tablet and anemia in Aranio Health Center. This research using analytic survey with cross sectional approach. Subject of this research are the pregnant women of trimester II and trimester III amount 52 respondents which are taken by total population. The result of the research showed that most of pregnant women were not obedient in consuming Fe tablet were 38 women (73,1%), Most of them with anemia that are 44 women (84,6%). The result of statistical using chi square test showed there is correlation between the obidience in consuming Fe tablets with anemia occurrence in the Work Area of Aranio Health Center (p value = 0,000). Midwifes as care provider have to motivate the pregnant woment to understand about how important to consume Fe tablet during pregnancy in order to decrease anemia occurrence to the pregnant women.